PENGARUH MODEL CREATIVE PROBLEM SOLVING BERBASIS TEKNOLOGI INFORMASI TERHADAP HASIL BELAJAR FISIKA SISWA SMA - TIKA SUPRIATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This research was aimed to find the effect of model of creative problem solving based on information technology on the outcomes of Physics Learning of senior high school students. This research was conducted at SMA 76 Jakarta class X. As for the samples in this research were X.7 and X.5 graders, each consisting of 35 students. Experimental classes were taught using a model of creative problem solving based on information technology. While the control classes were taught without using a model of creative problem solving based on information technology. The research method used was quasi experimental design with Nonequivalent Control Group Design. To measure the dependent variable used instrument in the form of multiple choice questions about as many as 25. The mean score of post test learning outcomes of students in the experimental class at 74.20 while the control class at 67.80. Hypothesis testing using t-test with significance level ? = 0.05 is obtained tcount = 2.777 and ttable = 1.668, that means Ho is rejected and H1 is accepted. From the results of this research concluded that there is significant influence model of creative problem solving based on information technology on the outcomes of physics learning of senior high school students. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh model creative problem solving berbasis teknologi informasi terhadap hasil belajar fisika siswa SMA. Penelitian ini dilakukan di SMA Negeri 76 Jakarta kelas X. Adapun yang menjadi sampel dalam penelitian ini adalah siswa kelas X.5 dan X.7 yang masing-masing terdiri dari 35 siswa. Kelas eksperimen diajar dengan menggunakan model creative problem solving berbasis teknologi informasi. Sedangkan kelas kontrol diajar tanpa menggunakan model creative problem solving berbasis teknologi informasi. Metode penelitian yang digunakan adalah quasi eksperimen dengan desain Nonequivalent Control Group Design. Untuk mengukur variabel terikat digunakan instrumen berupa soal pilihan ganda berjumlah 25 soal. Nilai rata-rata post test hasil belajar siswa pada kelas eksperimen sebesar 74,20 sedangkan pada kelas kontrol sebesar 67,80. Pengujian hipotesis menggunakan uji-t dengan taraf signifikansi ?=0,05 diperoleh thitung = 2,777 dan ttabel = 1,668 yang berarti Ho ditolak dan H1 diterima. Dari hasil penelitian dapat disimpulkan bahwa terdapat pengaruh signifikan model creative problem solving berbasis teknologi informasi terhadap hasil belajar fisika siswa SMA.